Hubungan Peran Tim Pencegahan dan Pengendalian Infeksi dengan Kepatuhan Perawat dalam Melakukan Hand Hygiene di Ruang Rawat Inap RS Harapan Bunda - Nurul Fitrah Fauziah; Solehudin Solehudin; Inas Syabanasyah (Jurnal Anestesi, 2025)
HAI's is an infection that patients get when using health facilities or undergoing treatment in hospitals that when they enter the incubation period. Hand hygiene is a term used to wash hands, there are two ways that can be used in washing hands, namely using alcohol-based hand sanitizers and soap. The type of research used is correlation analysis with a cross sectional research design. The sampling technique uses total sampling. The data collection technique used a questionnaire of 22 questions and an observation sheet of five moments and six steps of hand hygiene. The research sample was 70 respondents. Therefore, it was concluded that there was a significant relationship between the role of the Infection Prevention and Control Team and nurses' compliance in carrying out hand hygiene in the inpatient room of Harapan Bunda Hospital.